Morphology of the main bile ducts, with special reference to their musculature - Louw, JH (Department of Human Biology, 2025)
A thorough search of the ngliah, American nd Continental literature showe th t there is no comprehen• eiYe tr atise on the torm and structure of' th main bile ducta. Numerous oontributiona on different as ecta of the subject re constantly being added to the literature. ading theae articles, which re widely-scattered throughout the literature, indicates the neceasity tor integration and clarification of the v rioua taota reported. Import• ant anatomical tacta are not well•known; opinions on the musculature of the bile duota ditter; and the factora that have influenced and determined the torm and structure of the human bile duct• are but oorly underetood . Thia theaia eeeks to correlate, clarify and present in compact form the findinga of various 1nveat1sat1ons on the form and atruoture of the in bile ducts. Particular attention ia devoted to obeervationa on the musculature of the ducts. While the main du.:t:ta form the principal theme of thie study. thereat ot the extrahepatic biliary ayatem reoeivea such attention aa is thought neceaaary to produ<Ma a logical and balanced understanding of the subject.